Wayside School is falling down - Sachar, Louis, 1954-; Heitz, Tim (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
More humorous episodes from the classroom on the thirtieth floor of Wayside School, where students learn to tango, face the cafeteria's dreaded mushroom surprise, and study a hobo during show-and-tell.
"Ages 8-12"--Back cover.
3.9
3-6.
3-6
Keywords: Humorous stories; Schools -- Juvenile fiction; Humorous stories; Schools -- Fiction; Humorous fiction; School stories; Humorous fiction; School fiction